Cardiac beta1-adrenoceptor autoantibodies in human heart disease: rationale and design of the Etiology, Titre-Course, and Survival (ETiCS) Study - Deubner, Nikolas Maximilian; Berliner, Dominik; Schlipp, Angela; Gelbrich, Götz; Caforio, Alida L. P.; Felix, Stephan B.; Fu, Michael; Katus, Hugo; Angermann, Christiane E.; Lohse, Martin J.; Ertl, Georg; Störk, Stefan; et al. (European journal of heart failure, 2010)
AIMS: Evidence for a pathophysiologic relevance of autoimmunity in human heart disease has substantially increased over the past years. Conformational autoantibodies stimulating the cardiac beta1-adrenoceptor (beta1-aabs) are considered of importance in heart failure development and clinical pilot studies have shown their prognostic significance in human 'idiopathic' cardiomyopathy. - METHODS: We recently developed a novel highly sensitive fluorescence-based functional assay to detect stimulating beta1-aabs. We will use this method to assess Etiology, Titre-Course, and effect on Survival (ETiCS) of beta1-aabs in a prospective multicentre study with serial follow-up of patients after a first acute myocarditis or myocardial infarction. Several European core laboratories will jointly study the hypothesis that both disorders may trigger autoimmune reactions leading to the generation of beta1-aabs and/or other heart-directed aabs. Further, sera from healthy controls and well-characterized patient cohorts with dilated, ischaemic, or hypertensive cardiomyopathy will be analysed retrospectively for beta1-aab prevalence, incidence, persistence, and/or clearance. - CONCLUSION: ETiCS is so far the largest clinical diagnostic study projected to address cardiac autoimmunity. It attempts to unravel the pathophysiology of cardiac autoantibody formation and persistence/clearance. ETiCS will enhance current knowledge on autoimmunity in human heart disease and promote endeavours to develop novel therapies targeting cardiac aabs.
Online publish-ahead-of-print 21 May 2010
Gesehen am 31.01.2024